Analysis of Perceptions and Aspects of Ease of Transaction Using BYOND Mobile Banking by BSI - Mahrani, Dita; Harahap, Raja Sakti Putra (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2025)
This study aims to analyze user perceptions of the ease of transactions using the mobile banking applications BYOND by BSI. The research identifies several aspects influencing user comfort and ease of use, including functionality, transaction speed, security, and user interface convenience. The method used is a survey with a questionnaire distributed to users of both applications. The findings show that users of BYOND and BY BSI are generally satisfied with the ease and features offered by both apps, although some security issues still need improvement. Based on these findings, it is recommended that app developers continue to make improvements, particularly in security and user experience to support wider adoption.